Synthesis of novel CaF2 − CaO − Na2O − B2O3−SiO2 bioglass system: phase transformation, surface reaction and mechanical properties - Loh, Zhi Wei; Zaid, Mohd Hafiz Mohd; Matori, Khamirul Amin; Cheong, Wei Mun; Mayzan, Mohd Zul Hilmi; Hisam, Rosdiyana (Springer Science and Business Media LLC, 2024)
This research aims to investigate the potential of novel CaF2 − CaO − Na2O − B2O3−SiO2 glass systems and converted to bioactive glass-ceramics. The study involves examining the effects of different heat treatment temperatures and immersion periods, with the goal of exploring these materials as viable alternatives for various biomedical applications. A typical melt-quenching technique was used to synthesize the glass samples, followed by a controlled heat treatment. The main crystalline phases are cuspidine and wollastonite, which have the potential to promote bioactivity, especially in dental and bone-related applications. The sample heat-treated at 700 °C showed an increased microhardness and fracture toughness by more than 116% and 36%, compared to the initial value. Furthermore, the increase in pH and the observed weight loss/gain demonstrated the reactivity of the samples with the phosphate buffer-saline medium, indicating their bioactive properties. Remarkably, the microhardness and fracture toughness exhibited notable improvements after 14 days of immersion, with an enhancement of 4.71% and 4.66%, highlighting their potential durability and longevity in high-strength dental crown applications. Consequently, this research presents a promising method for developing sustainable novel glass and glass-ceramic materials devoid of phosphates. These materials boast enhanced mechanical properties while preserving bioactivity, making them well-suited for dental implants and restorative purposes.